LINGVODIDACTIC LEARNING IN EDUCATION - Safarova Dildora,; Ismoilova Marjona,; Abirkulova Ozoda, (Ustozlar uchun, 2025)
This article examines four methods of foreign language learning: the Grammar and Translation Method, the Direct Method, the Audiolingual Method, and the Communicative Method. Each method is discussed in relation to its key characteristics and teaching approaches. Linguists' opinions are included to provide a critical evaluation of each method. The Grammar and Translation Method emphasizes reading and writing, the Direct Method highlights oral communication and natural language acquisition, the Audiolingual Method prioritizes repetition and memorization, while the Communicative Method focuses on meaningful communication and social interaction. By reviewing these methods and expert opinions, the article explores the implications of each approach in foreign language teaching.